Distinct In Vitro T-Helper 17 Differentiation Capacity of Peripheral Naive T Cells in Rheumatoid and Psoriatic Arthritis - Baricza, Eszter; Marton, Nikolett; Királyhidi, Panna; Kovács, Orsolya Tünde; Kovácsné Székely, Ilona; Lajkó, Eszter; Kőhidai, Lászó; Rojkovich, Bernadett; Érsek, Barbara; Buzás, Edit Irén; Nagy, György (Frontiers in Immunology, 2018)
Background: The Th17 cells have a prominent role in inflammation as well as in bone and join destruction in both rheumatoid and psoriatic arthritis (RA, PsA). Here we studied Th17 cell differentiation in RA and PsA. Methods: Blood samples from healthy donors, RA and PsA patients were collected. CD45RO- (naive) and CD45RO+ (memory) T cells were isolated from PBMC by magnetic separation. Naive T cells were stimulated with anti-CD3, anti-CD28 and with goat anti-mouse IgG antibodies and treated with TGFβ, IL-6, IL-1β and IL-23 cytokines and with anti-IL-4 antibody. IL-17A and IL-22 production were measured by ELISA, RORC and TBX21 expression were analysed by qPCR and flow cytometry. CCR6, CCR4 and CXCR3 expression were determined by flow cytometry. Cell viability was monitored by impendance-based cell analyzer (CASY-TT). Results: RORC, TBX21, CCR6 and CCR4 expression of memory T cells of healthy individuals (but not RA or PsA patients) were increased (p<0.01; p<0.001; p<0.05; p<0.05, respectively) compared to the naive cells. Cytokine-induced IL-17A production was different in both RA and PsA patients when compared to healthy donors (p=0.0000026 and p=0.0001047, respectively). By contrast, significant differences in IL-22 production were observed only between RA versus healthy or RA versus PsA patients (p=0.000006; p=0.0013454, respectively), but not between healthy donors versus PsA patients. Conclusions: The naive CD4 T-lymphocytes are predisposed to differentiate to Th17 cells and the in vitro Th17-cell differentiation is profoundly altered in both RA and PsA.